Facilitating Access to Higher Education for People Seeking Asylum in Australia: Institutional and Community Responses - Burke, Rachel; Fleay, Caroline; Baker, Sally; Hartley, Lisa; Field, Rebecca (Refuge: Canada's Journal on Refugees, 2020)
Higher education remains unattainable for many people seeking asylum in Australia, where temporary visa status renders individuals ineligible for a range of government services including assistance with financing tertiary study. Many universities have responded by offering scholarships and other essential supports; however, our research indicates the challenges associated with studying while living on a temporary visa can affect the success of educational assistance. Here we highlight the importance of scholarships and other supports for facilitating access to tertiary study, particularly given the continuation of restrictive government policies, and identify the need for people seeking asylum to inform institutional and community responses. **** Note that the pagination of this article has been adjusted due to resolving a production error in another article in this issue.***